PERAN PENDIDIKAN AGAMA KRISTEN DALAM MEMBENTUK KEPEMIMPINAN KRISTIANI YANG BERINTEGRITAS - Yensy Toding Buli; Selmi pallangan, Lisa Dwipramita, Renita pasang, Devi Dawa (ADISAM PUBLISHER, 2025)
Christian Religious Education plays an important role in shaping Christian leadership with integrity. Leadership from a Christian perspective emphasizes not only managerial skills, but also a strong moral and spiritual foundation based on biblical teachings. This article discusses how Christian Religious Education can be an effective means of shaping leaders who have Christ-like characters, such as humility, honesty, responsibility, and concern for others. Through a value-based learning approach, spiritual reflection, and implementation of biblical leadership principles, it is hoped that a generation of leaders will be born who are not only competent, but also have a vision and mission to serve with love. Thus, Christian religious education is not just doctrinal teaching, but also a process of character formation that has a real impact on leadership in various aspects of life. Christian Religious Education, Christian Leadership, Character